Mediators of the Association Between Driving Cessation and Mortality Among Older Adults. (December 2013) - O'Connor, Melissa L.; Edwards, Jerri D.; Waters, Martinique P.; Hudak, Elizabeth M.; Valdés, Elise G.
Objective: The present study examined health and physical performance as mediators of the association between driving cessation and mortality among older residents of small and large cities.Method: Participants ( N = 2, 793) were from the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) study. Participants' driving status and health were measured at baseline, and mortality rates were observed across the subsequent 5 years.Results: Overall, mortality risk was 1.68 times higher for nondrivers versus drivers; this relationship was significantly mediated by physical performance and social, physical, and general health. For large-city residents, mediation effects for all mediators were significant and complete. For small-city residents, only physical and general health were significant mediators, and these effects were partial.Discussion: Health difficulties that accompany or follow driving cessation may explain the association between driving cessation and mortality, particularly for residents of large cities, where alternative transportation options may be more numerous.